2006
DOI: 10.1111/j.1600-051x.2006.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Nine‐ to fourteen‐year follow‐up of implant treatment. Part III: factors associated with peri‐implant lesions

Abstract: Individuals with a history of periodontitis and individuals who smoke are more likely to develop peri-implant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
333
3
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(377 citation statements)
references
References 22 publications
30
333
3
11
Order By: Relevance
“…[14][15][16][17] However, in the current study, there was minimal incidence of peri-implantitis, a chronic inflammatory condition similar to periodontitis that results in bone loss around implants. Although this study was carried out in a periodontal practice, susceptibility to aggressive periodontitis was recorded in patients receiving only 4.1 per cent of the implants, and only 3.4 per cent of the study patients were classified as heavy smokers, there were no patients who belonged to both groups.…”
Section: Discussionmentioning
confidence: 96%
“…[14][15][16][17] However, in the current study, there was minimal incidence of peri-implantitis, a chronic inflammatory condition similar to periodontitis that results in bone loss around implants. Although this study was carried out in a periodontal practice, susceptibility to aggressive periodontitis was recorded in patients receiving only 4.1 per cent of the implants, and only 3.4 per cent of the study patients were classified as heavy smokers, there were no patients who belonged to both groups.…”
Section: Discussionmentioning
confidence: 96%
“…[2][3][8][9] One study 6 reported a correlation between the presence of keratinized tissue, plaque levels and the incidence of mucositis, and theorized that sites with minimal keratinized tissue might be prone to a lower incidence of periodontal pocket formation. 3,10 In the anterior maxilla, however, the contribution of thick, keratinized gingiva to implant esthetics has not been disputed. As a general rule, some clinicians anticipated that 1 mm of gingival recession could be expected from the time of abutment connection M A N U S C R I P T…”
Section: Introductonmentioning
confidence: 99%
“…Increased probing depths, plaque indices and bleeding on probing values have been observed in smoker sub-jects restored with dental implants. A systematic review of the literature that assessed implant loss, bone loss greater than 50%, implant mobility, persistent pain, or peri-implantitis, reported that smokers had a significantly enhanced risk of peri-implantitis (21). The aim of the present study was to evaluate the impact of smoking and previous periodontal disease on the microbiota and peri-implant health in a group of partial edentulous patients restored with dental implants.…”
Section: Smoking and Dental Implant Failurementioning
confidence: 93%